Isu dan Analisis Kebijakan Pendidikan Masa Depan (Review dan Revitalisasi Kebijakan Pendidikan Islam di Ma’had Aly) - Syarifatul Marwiyah; Mohammad dasuki (FALASIFA : Jurnal Studi Keislaman, 2021)
In the dynamics of pesantren education, the development of Islamic boarding schools has undergone changes and shifts in several aspects along with the progress of the times and the development of science and technology. Islamic boarding schools are slowly adopting formal educational institutions to maintain the image of the Islamic boarding schools and to maintain or increase the number of students living in the Islamic boarding schools. Ma'had Aly when viewed from the map of education including formal diniyah education, in this case the Government issued several policies related to Islamic Religious Education in Ma'had Aly. The whole series of higher education systems in the style of pesantren (Ma'had Aly) in an effort to create ulama 'which is currently a rare thing, the pesantren with a spirit of independence are able to boost back religious education that is tafaqquh fi al-din. Therefore, the government should pay more attention to providing support and assistance that is equivalent to other Islamic higher education. Keyword: Education Policy and Ma'had Aly Dalam dinamika pendidikan pesantren perkembangan pondok pesantren telah mengalami perubahan dan pergeseran dalam beberapa aspek seiring kemajuan zaman dan perkembangan ilmu pengetahuan dan teknologi. Pondok pesantren perlahan-lahan mengadopsi lembaga pendidikan formal untuk mempertahankan citra pondok pesantren serta memepertahankan atau menambah jumlah santri yang bermukim di pondok pesantren. Ma’had Aly jika dilihat dari peta pendidikan termasuk pendidikan diniyah formal, dalam hal ini Pemerintah mengeluarkan beberapa kebijakan-kebijakan terkait Pendidikan Agama Islam yang ada di Ma’had Aly. Seluruh rangkaian dari sistem pendidikan tinggi ala pesantren (Ma’had Aly) dalam upaya menciptakan ulama’ yang pada saat ini merupakan hal yang langka, maka pesantren dengan jiwa kemandiriannya mampu mendongkrak kembali pendidikan agama yang tafaqquh fi al-din. Oleh karena itu pemerintah seharusnya lebih memperhatikan dengan memberikan dukungan dan bantuannya yang setara dengan pendidikan tinggi islam lainnya. Kata Kunci: Kebijakan Pendidikan dan Ma’had Aly